2002
DOI: 10.1007/s00066-002-0926-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo at the Sites of Irradiation in a Patient with Hodgkin's Disease

Abstract: Complete radiation-induced depigmentation of skin from patients suffering from vitiligo is a side effect of radiation therapy. Patients should be informed about this side effect by the radiooncologist. Preventing the loss of depth of the build-up dose region might improve the cosmetic results of radiation therapy in patients with history of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…Pajonk F et al, had reported about a patient who was treated with radiotherapy for Hodgkin's disease [6]. He had a 25 year history of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pajonk F et al, had reported about a patient who was treated with radiotherapy for Hodgkin's disease [6]. He had a 25 year history of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned case reports [3][4][5][6] had patients with preexisting vitiligo. Patients with prior history of vitiligo have increased risk of developing depigmentation in the radiotherapy portal area.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of melanocytes in the irradiated skin has been demonstrated by Pajonk et al and correlated with the dose-dependent decrease in the red/green and yellow/blue saturation and overall increase in brightness on colorimetry. [9] Free radical-mediated damage, induced by radiotherapy, may be the initial pathogenic event in melanocyte degeneration in the irradiated skin. The early cell death of melanocytes in vitiligo is related to their increased sensitivity to the oxidative stress caused by irradiation, which may arise from complex processes of abnormal synthesis and processing of tyrosinaserelated protein-1 and its interaction with calnexin.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo was reported at the sites of irradiation in a patient with Hodgkin's disease [8] . The patient was 37 years old with a 25-year history of vitiligo.…”
Section: Radiotherapymentioning
confidence: 99%
“…Depigmentation has only rarely been reported in association with irradiation (Koebner phenomenon), and it was documented in a few vitiligo patients and in patients with metastatic melanoma [8][9][10][11] .…”
Section: Radiotherapymentioning
confidence: 99%